If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + -1 = -1x Reorder the terms: -1 + y = -1x Solving -1 + y = -1x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + y = 1 + -1x Combine like terms: -1 + 1 = 0 0 + y = 1 + -1x y = 1 + -1x Simplifying y = 1 + -1x
| 3x+2=y | | [x-17]=21 | | 17.3x+2=2 | | y+2x=x^2-1 | | 5a+ax=17 | | 2(-z+3)=-4 | | 49x^2+16=0 | | -2(k-2)=-4 | | 1+6x=21x | | 2(-2n-1)=6 | | 110-3x=4x+5 | | 9+2(y-4)=13 | | x^2+4x-21= | | -2(a+4)=-4 | | -3z+8=-1 | | e^2x=27 | | -43-3x=9x+21 | | 2(k+3)=10 | | (4x^2-3x)(5x^2-6x+2)= | | 2x=23 | | (3x-5)(3x+5)= | | 2(2b-1)=14 | | (3x^3-4x^2+x-2)-(x^3-5x^2+3x+2)= | | c=10+30 | | c=a+30 | | 8(b-8)= | | 4(w-5)=36 | | 8=-3u-4 | | x+23=0 | | (x^4-5x^3+7x^2-4x+3)(x-3)= | | 5(2x-4)=4(x-8) | | 5x+4=2x+25 |